Pathogenic role of PFKFB3 in endothelial inflammatory diseases - Zhou, Ling; Li, Juan; Wang, Juanjuan; Niu, Xuping; Li, Junqin; Zhang, Kaiming (Frontiers in Molecular Biosciences, 2024)
Abstract：The differentiation of vascular endothelial cells and the formation of new blood vessels are inseparable from the energy supply and regulation of metabolism.The budding of blood vessels is a starting point of glycolysis pathway in angiogenesis.Phosphofructokinase-2 /fructose 2,6-biophosphatase 3 (PFKFB3), a key rate-limiting enzyme in glycolysis, exhibits strong kinase activity. Inhibition of PFKFB3 can reduce the rate of glycolysis, thereby inhibiting the budding of blood vessels, resulting in inhibition of pathological angiogenesis. In this review, the role of PFKFB3 in the angiogenesis of inflammatory diseases was summarized, and the endothelial inflammatory diseases associated with PFKFB3 were reviewed.